2019
DOI: 10.1002/app.48468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas‐phase tortuosity on the mechanical properties of low‐density polyolefin open‐cell foams at low‐ and high‐strain rates

Abstract: This paper describes the mechanical behavior in compression, at both low-and high-strain rates, of several low-density open-cell polyolefin-based foams with different gas phase interconnectivities and different levels of gas-phase tortuosity. The mechanical properties of the open-cell polyolefin foams have been compared with two different references: an open-cell low tortuous foam based on flexible polyurethane and closed-cell polyolefin foams. One the one hand, at low-strain rates, it has been observed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thus, numerous nanosized cells appear on the large cell walls. The local open-cell structure could weaken the compressive mechanical properties of the PLLA foams. , For the PLLA/PDLA blend foams, no local open-cell structure can be observed in the wall because the cell walls are hard to be broken during the process of being stretched and thinned because of the reinforcement effect of the SC crystallites.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, numerous nanosized cells appear on the large cell walls. The local open-cell structure could weaken the compressive mechanical properties of the PLLA foams. , For the PLLA/PDLA blend foams, no local open-cell structure can be observed in the wall because the cell walls are hard to be broken during the process of being stretched and thinned because of the reinforcement effect of the SC crystallites.…”
Section: Resultsmentioning
confidence: 99%
“…There are also several studies on the dynamic mechanical investigation of polymer foams, which primarily focus on the study of the effect of air between foam cells and foam density. Lopez Gonzalez et al 21 studied the effect of open‐cell content on same density low density polyethylene and ethylene‐vinyl acetate foams and showed that at high deformation rates, an open‐cell foam with high tortuosity approaches the properties of closed‐cell foams, wherein the compression of gas in the cells improves the shock‐absorbing capability of the foam. (Tortuosity gives the required distance, which a gas molecule has to move to get from one side of the foam to the other).…”
Section: Introductionmentioning
confidence: 99%
“…The particles of Zinc Oxide act as colloidal particles, encouraging the creation of additional bubbles, and this appears to rise with filler content. Increasing viscosity appears to impede cell growth [19,20], lower concentration foams allow for easier cell growth, resulting in a lower final foam density [29]. The vacancy percentage and filling content impact foam density [30].…”
Section: Polyurethane Foam Synthesismentioning
confidence: 99%
“…It is similar to foams with closed cells in that the gas in cells compresses, enhancing the foam's shock-absorbing ability (Lopez Gonzalez. [19]). (A gas-phase must travel a long distance to traverse a foam.)…”
Section: Introductionmentioning
confidence: 99%